Genomic selection analysis of morphological and adaptation traits in Chinese indigenous dog breeds - Li, Yangfeng; Huang, Min; Wang, Zhenjie; Liu, Xueyuan; He, Shan; Wang, Tao; Ma, Baicheng; Liu, Jianyun; Li, Xingnuan; Xiong, Jianjun; Hua, Jinlian; Ye, Junhua; et al. (Frontiers in Veterinary Science, 2023)
The significant morphological differences and abundant germplasm resources of Chinese indigenous dog breeds can be attributed to the diverse geographical environment, including plateaus, mountains, and a long history of raising dogs. The combination of both natural and artificial selection during the past several thousand years has led to hundreds of dog breeds with distinct morphological traits and environmental adaptations. China is one of the earliest countries to domesticate dogs and there are more than 50 ancient indigenous dog breeds. In this study, the run of homozygosity (ROH) and proportion of the autosomal genome covered by ROHs were calculated for 10 dog breeds that are the most representative Chinese indigenous dogs based on 170K SNP microarray. The results of FROH showed that the Chuandong hound dogs (HCSSC) have the highest level of inbreeding among the tested breeds. The inbreeding in HCSSC occurred more recently than the Liangshan dogs (SCLSQ) dogs because of more numbers of long ROHs in HCSSC dogs, and the former also have higher inbreeding degree. In addition, there are significant differences in the inbreeding degree among different subpopulations of the same breed, such as the Thin dogs from Shaanxi and Shandong Province. To explore genome-wide selection signatures among different breeds, including coat color, ear shape, and altitude adaptability, we performed genome selection analyses of FST and cross population extended haplotype homozygosity. For the coat color, the FST analysis between Xiasi dogs (XSGZ) and HCSSC dogs was performed and identified multiple genes involved in coat color, hair follicle, and bone development, including MC1R, KITLG, SOX5, RSPO2, and TBX15. For the plateau adaptability, we performed FST and XP-EHH analyses between dogs from Tibet (Tibetan Mastiffs and Nyingchi dogs) and plain regions (Guangxi Biwei dogs GXBWQ and Guandong Sharpei dogs). The results showed the EPAS1 gene in dogs from Tibet undergo strong selection. Multiple genes identified for selection signals based on different usage of dogs. Furthermore, the results of ear shape analyses showed that MSRB3 was likely to be the main gene causing the drop ear of domestic dogs. Our study provides new insights into further understanding of Chinese indigenous dogs.